A study of consumer's attitude towards viral advertising on social media: a case study in an ice cream manufacturing company - Mohammad, Noorita; Abdul Rahman, Zanariah; Mohammad, Mardhiah; Nik Mustapaha, Nik Nur Shahira (2019)
With the explosive growth of social media in recent years, viral advertising seems the best tool to release promotional message activities through interactive network based channel. This study investigated the effect of viral advertising as marketing strategy by an ice cream manufacturing company, Al Jazeera Sdn Bhd. The company had very little experience in viral advertising and has been relying in conventional marketing strategies for many years. Thus, it is crucial for the company to assess consumer’s perception toward their current advertising strategy, which plays a crucial role in brand awareness of the company. This study aimed to determine relationships between factors such as perception of informative, entertainment, irritation and source credibility on consumer’s attitudes towards viral advertising. In the study, data were collected from 115 respondents, which questionnaires were distributed on social media platforms. Then, the data were analysed using SPSS (Statistical Package for the Social Sciences). The findings revealed significant relationship between consumer’s attitudes and two of the factors being studied which were informative and entertainment perceptions. In conclusion, marketers need to understand the effect of viral advertising because it will shape the dynamics of the business marketing strategy. Hence to cope with the rapid advancement of the technology, marketers need to be more creative in conveying the messages that would reach their consumers.